Some new methods for comparing the capability of two processes using process capability index Cpm. Issue 5 (24th June 2021) - Perakis, Michael
Abstract : Purpose: The purpose of the paper is the construction of confidence intervals for the ratio of the values of process capability index C pm for two processes. These confidence intervals can be used for comparing the capability of any pair of competitive processes. Design/methodology/approach: Two methods for constructing confidence intervals for the ratio of the values of process capability index C pm for two processes are proposed. The suggested techniques are based on a two-step approximation of the doubly non-central F distribution. Their performance is tested via simulation. Findings: The performance of the suggested techniques seems to be rather satisfactory even for small samples, as illustrated through the use of simulated data. Practical implications: The practical implication of the suggested techniques is that they can be implemented in real-world applications, since they can be used for comparing the capability of any pair of competitive processes. Originality/value: The paper presents two new methods for constructing confidence intervals for the ratio of the values of process capability index C pm for two processes.